2019
DOI: 10.1111/febs.15007
|View full text |Cite
|
Sign up to set email alerts
|

APEX2‐mediated proximity labeling resolves protein networks in Saccharomyces cerevisiae cells

Abstract: Enzyme‐catalyzed proximity labeling (PL) with the engineered ascorbate peroxidase APEX2 is a novel approach to map organelle compartmentalization and protein networks in living cells. Current procedures developed for mammalian cells do not allow delivery of the cosubstrate, biotin‐phenol, into living yeast cells. Here, we present a new method based on semipermeabilized yeast cells. Combined with stable isotope labeling by amino acids in cell culture (SILAC), we demonstrate proteomic mapping of a membrane‐enclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
(98 reference statements)
1
15
0
Order By: Relevance
“…Since its invention in 2013, APEX labeling has complemented classic fractionation-based methods to provide a comprehensive proteomic map of the mitochondria (Hung et al, 2014(Hung et al, , 2017Rhee et al, 2013), signaling complexes (Paek et al, 2017), RNA granules (Markmiller et al, 2018), etc., in the live cell context. Notably, a majority of APEX applications are in metazoan cells, with only a few examples in microorganisms, such as yeast cells (Hwang and Espenshade, 2016;Santin et al, 2018;Singer-Kr€ uger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its invention in 2013, APEX labeling has complemented classic fractionation-based methods to provide a comprehensive proteomic map of the mitochondria (Hung et al, 2014(Hung et al, , 2017Rhee et al, 2013), signaling complexes (Paek et al, 2017), RNA granules (Markmiller et al, 2018), etc., in the live cell context. Notably, a majority of APEX applications are in metazoan cells, with only a few examples in microorganisms, such as yeast cells (Hwang and Espenshade, 2016;Santin et al, 2018;Singer-Kr€ uger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast is a powerful model organism for studying eukaryotic cell biology (Duina et al, 2014;Pan, 2011). However, APEX labeling has not been successful in yeast due to the poor cellular permeability of its BP substrate (Hwang and Espenshade, 2016;Singer-Kr€ uger et al, 2020). To facilitate probe penetration, the yeast cell wall had to be partially destroyed via the action of zymolase (Hwang and Espenshade, 2016) or freeze-thaw cycle (Singer-Kr€ uger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even though biotin‐phenol can be simply incubated with mammalian cells for cytosolic and mitochondrial protein labeling, a number of studies have shown that biotin‐phenol may not effectively penetrate membranes (Li et al, 2014; Rees et al, 2015). Moreover, special procedures are required for efficient delivery of biotin‐phenol and optimal proximity labeling in yeast (Hwang & Espenshade, 2016; Singer‐Kruger et al, 2020). Therefore, optimizing biotin‐phenol delivery to a region of interest in a specific cell type may be required to achieve successful protein labeling.…”
Section: Comparison Between Biotin Ligase‐based Peroxidase‐based Anmentioning
confidence: 99%
“…For yeast, removing the cell wall by zymolyase or osmotic shock allows the entry of biotin phenol (Hwang and Espenshade, 2016). Further optimization of the protocol by a different group enabled the proteomic mapping of the mitochondrial matrix and the nucleus (Singer-Krüger et al, 2019). As an example, fusion of APEX2 to the core H2B histone Htb1 identified Yer156c, a nuclear protein with unknown function previously not detected with traditional IP-MS approaches.…”
Section: Histone Variants and Post-translational Modificationsmentioning
confidence: 99%